Leveraging single-cell genomics to expand the fungal tree of life. (December 2018) - Ahrendt, Steven; Quandt, C.; Ciobanu, Doina; Clum, Alicia; Salamov, Asaf; Andreopoulos, Bill; Cheng, Jan-Fang; Woyke, Tanja; Pelin, Adrian; Henrissat, Bernard; Reynolds, Nicole; Benny, Gerald; et al.
Abstract Environmental DNA surveys reveal that most fungal diversity represents uncultured species. We sequenced the genomes of eight uncultured species across the fungal tree of life using a new single-cell genomics pipeline. We show that, despite a large variation in genome and gene space recovery from each single amplified genome (SAG), ≥90% can be recovered by combining multiple SAGs. SAGs provide robust placement for early-diverging lineages and infer a diploid ancestor of fungi. Early-diverging fungi share metabolic deficiencies and show unique gene expansions correlated with parasitism and unculturability. Single-cell genomics holds great promise in exploring fungal diversity, life cycles and metabolic potential. Single-cell genome sequencing of eight uncultured fungal species provides insights into the phylogenetic placement of early-diverging lineages, highlights metabolic deficiencies and identifies gene expansions correlated with parasitism and unculturability.